Legal and Regulatory Considerations in promoting Factoring as an Alternative Trade Financing Tool in Nigeria - Masamba, Magalie (University of Pretoria, 2021)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2021.